A cross-sectional study investigating the associations of person-organisation and person-group fit with staff outcomes in mental healthcare. Issue 9 (24th September 2019) - Herkes, Jessica; Ellis, Louise A; Churruca, Kate; Braithwaite, Jeffrey
Abstract : Objectives: Organisational and workplace cultures are fundamental determinants of health systems performance; through better understanding of the dimensions of culture there is the potential to influence them, and subsequently improve safety and quality of care, as well as the experiences of both patients and staff. One promising conceptual framework for studying culture in healthcare is person-environment (P-E) fit. Comprising person-organisational (P-O) and person-group (P-G) components, P-E fit is defined as the extent to which individuals are compatible with their work environment. The aim of this study was to examine the associations of P-O and P-G fit with staff outcomes in mental healthcare. Setting and participants: Participants (n=213) were staff and volunteers at 31 primary mental health facilities across six states of Australia. Primary and secondary outcome measures: Staff outcomes, comprising burnout (depersonalisation and emotional exhaustion), job satisfaction and work stress. Design: A multidimensional survey tool was used to measure P-O and P-G fit, and staff outcomes. Multiple regression analyses were used to test the associations between fit and outcome measures. Results: The regression analyses indicated that, based on a Bonferroni adjusted alpha value of α=00417, P-O fit accounted for 36.6% of the variability in satisfaction (F=8.951, p≤0.001); 27.7% in emotional exhaustion (F=6.766, p≤0.001); 32.8% in depersonalisation (F=8.646, p≤0.001); and 23.5% in work stress (F=5.439, p≤0.001). The P-G fit results were less conclusive, with P-G fit accounting for 15.8% of the variability in satisfaction (F=4.184, p≤0.001); 10.0% in emotional exhaustion (F=2.488, p=0.014); 28.6% in depersonalisation (F=8.945, p≤0.001); and 10.4% in work stress (F=2.590, p=0.032). There was no statistically significant increase in the variability accounted for when the interaction term of P-O and P-G fit was added to the regression. Conclusions: The findings highlight that staff's perception of their workplace and organisational culture can have implications for staff well-being.